Neutrophil breaching of the blood vessel pericyte layer during diapedesis requires mast cell-derived IL-17A - Joulia, Régis; Guerrero-Fonseca, Idaira María; Girbl, Tamara; Coates, Jonathon A.; Stein, Monja; Vázquez-Martínez, Laura; Lynam, Eleanor; Whiteford, James; Schnoor, Michael; Voehringer, David; Roers, Axel; Nourshargh, Sussan; et al. (Nature Communications, 2022)
Neutrophil diapedesis is an immediate step following infections and injury and is driven by complex interactions between leukocytes and various components of the blood vessel wall. Here, we show that perivascular mast cells (MC) are key regulators of neutrophil behaviour within the sub-endothelial space of inflamed venules. Using confocal intravital microscopy, we observe directed abluminal neutrophil motility along pericyte processes towards perivascular MCs, a response that created neutrophil extravasation hotspots. Conversely, MC-deficiency and pharmacological or genetic blockade of IL-17A leads to impaired neutrophil sub-endothelial migration and breaching of the pericyte layer. Mechanistically, identifying MCs as a significant cellular source of IL-17A, we establish that MC-derived IL-17A regulates the enrichment of key effector molecules ICAM-1 and CXCL1 in nearby pericytes. Collectively, we identify a novel MC-IL-17A-pericyte axis as modulator of the final steps of neutrophil diapedesis, with potential translational implications for inflammatory disorders driven by increased neutrophil diapedesis.